The Effect Of Human Capital And Workability On Employee Performance With Job Satisfaction As An Intervening Variable - Fadli Anugrah (International Journal of Business and Quality Research, 2025)
This research aims to determine the influence of human capital and workability on employee performance with job satisfaction as an intervening variable. The object of this research is in Food Security Office in Sungai Penuh City. The respondents in this study are civil servants at Food Security Office in Sungai Penuh City. With a total of 30 people. Based on the results of the previous analysis and discussion, the following can be concluded as follows: human capital and workability influence the large hall of the Food Security Office in Sungai Penuh City because t count > t table (1.02>0.05). Job satisfaction influences the performance of employees at the Food Security Office in Sungai Penuh City because t count > t table (0,38 > 0.05). Human capital influences job satisfaction. This is proven by t count > t table (1.63>0.05). Workability affects job satisfaction. This is proven by t count > t table (1.29>0.05) job satisfaction has no effect as an intervening variable between human capital on the performance of employees at Food Security Office in Sungai Penuh City. This is proven by t count < t table (-0.22<0.05).